High-speed train Oslo-Berlin - Jespersen, Per Homann (Proceedings from the Annual Transport Conference at Aalborg University, 2007)
The COINCO-project (Corridor of Innovation and Cooperation), a collaboration between cities and regions in the Oslo-Göteborg-Malmö-Copenhagen-Berlin corridor, was developing a common strategy aimed at furthering growth through cooperation and use of complementary strengths. Project proposals was developed within a number of areas covering innovation (e.g. in creative industries and sustainable energy), institutional cooperation (university cooperation, planning education) as well as transport infrastructure (Jespersen et al. 2006). On the infrastructure part very much emphasis was put into establishing functioning transnational railroads for passengers and freight. The reason for this was that among the four main transport modes – air, sea, road and rail – the forsyning of infrastructure for the first three are in general well provided for in the four countries; air and sea through the market and road through national programs. The railway sector, however, is due to its organisation oriented towards serving national transport, and because of the poor economy of most lines, transnational routes have had low priority. The one exception in the corridor, the Øresund connection between Copenhagen and Malmö has however shown, that conventional wisdom within this field might no longer be valid. In this paper a pre-feasibility study of a high-speed connection between Oslo and Berlin is presented as well as some of the considerations made for making this connection feasible as well as attractive for the decision makers.